Genetic variability among Anopheles species belonging to the Nyssorhynchus and Anopheles subgenera in the Amazon region Variabilidade genética entre espécies de Anopheles dos subgêneros Nyssorhynchus e Anopheles da região Amazônica - Raquel Borges Moroni; Juracy de Freitas Maia; Wanderli Pedro Tadei; Joselita Maria Mendes dos Santos (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Isoenzymatic analyses were performed involving species of the Nyssorhynchus and Anopheles subgenera in order to estimate the intra and interspecies genetic variability. METHODS: Mosquitoes were caught at different localities in the Amazon region. The collection and rearing of mosquitoes in the laboratory followed specific protocols. For the genetic variability analyses, the technique of horizontal electrophoresis on starch and starch-agarose gel with appropriate buffer systems was used. The alloenzyme variation was estimated using the Biosys-1 software. RESULTS: Out of the 13 loci, eight were polymorphic. Anopheles nuneztovari presented the largest number of alleles per locus, while the smallest number was detected in Anopheles marajoara from Macapá. The largest number of polymorphic loci was found for Anopheles marajoara from Maruanum and the smallest for Anopheles benarrochi (Guayará Mirim). Anopheles darlingi (Macapá) presented the greatest heterozygosity (Ho = 0.167 ± 0.071), while the lowest heterozygosity (Ho = 0.045 ± 0.019) was observed in Anopheles intermedius (Pacoval) of the subgenus Anopheles. Wright's F coefficient revealed considerable genetic structuring between the populations of Anopheles darlingi (Fst = 0.110) and between the populations of Anopheles marajoara (Fst = 0.082). CONCLUSIONS: Considering all the species studied, the genetic distance ranged from 0.008 to 1.114. The greatest distance was between Anopheles mattogrossensis and Anopheles oswaldoi, while the smallest was between the Anopheles benarrochi populations. INTRODUÇÃO: Análises isoenzimáticas foram realizadas envolvendo espécies dos subgêneros Nyssorhynchus e Anopheles para estimar a variabilidade genética intra e interespecífica. MÉTODOS: Os mosquitos foram capturados em diferentes localidades da região Amazônica. A coleta e a criação dos mosquitos em laboratório foram conforme protocolos específicos. Na análise da variabilidade genética empregou-se a técnica de eletroforese horizontal em géis de amido e ...